Attribution of achievement motivation and academic performance achievement in mathematics - Ruiz Sánchez, Gabriela (2015)
Attribution of the relationship between achievement motivation and academic performance in mathematics, in a sample of 993 high school students, using a descriptive correlational design was studied. With that goal were administered the Attributional Achievement Motivation Scale, EAML (Manassero and Vasquez, 1998-2000) and a report of self-perceived academic performance, being a direct and highly significant covariation between academic performance and causal attribution Grounds achievement in mathematics and its components. Concluding that academic performance is related to the interest in the course, the attribution of results to effort, hoping to get a certain result, the influence of the tests in the note and the ability of the teacher.